NUTRITION COUNSELING AND NUGGET PROCESSING TO PREVENT STUNTING IN TEWANG KARANGAN VILLAGE, KATINGAN - Lilis Rosmainar; Nurhaliza (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2023)
Stunting is a condition of chronic malnutrition in children which can impact children's motor and verbal development as well as affect their cognitive development and productivity in adulthood. The prevalence of stunting in Indonesia in 2021 was 24.4%, while the prevalence rate of stunting in Central Kalimantan in 2021 was 27.4% and decreased in 2022 to 26.9%. There has been a decrease in the stunting prevalence rate of around 0.5%, but this reduction still needs to be improved so that there is an acceleration in the reduction in the stunting rate. The aim of carrying out this activity is to provide education regarding the dangers of stunting in children and efforts to prevent stunting through training in developing potentially nutritious food innovations to prevent stunting, so that it can accelerate the reduction in stunting rates and become a solution for local communities in improving their standard of living. The method used in this activity is a lecture using slide media and practice in making nutritious food for toddlers. The results of the outreach show that the community understands the dangers of stunting on children's growth and development and the community is able to innovate nutritious food for toddlers.